TCH-038 Shortage of Sterile Calcium Gluconate Stock Solution For Parenteral Nutrition: What is the Alternative and How Much Does It Cost?. (12th March 2013) - Siorat, V; Serrano, S; Jorret, P; Vaconsin, P; Brion, F; Storme, T; Perrinet, M
Abstract : Background: The Total Parenteral Nutrition (TPN) production facility of our children's hospital produces around 20, 000 units per year with 2 Baxa EM2400 compounders. In June 2012, a shortage of the calcium source (10% sterile solution of calcium gluconate in 500 mL bottles) occurred. To overcome this problem, we first tried to import an alternative source but the administrative delay was too long. The only sources available within a month were 10 mL plastic or glass ampoules. The estimated consumption was around 300 ampoules per production day. To maintain efficiency and safety in the TPN facility, it was decided to produce calcium gluconate bags from 10 mL ampoules by sterilising filtration to maintain the safety of preparation. Purpose: To evaluate the additional cost incurred by setting up this production and the increased time required. Materials and Methods: The pharmacy prepared calcium gluconate bags (250 mL) from plastic ampoules after filtration (0.22 µm philtres (Sterivex Millipore), using a Repeater Pump (Baxter), in a laminar air flow cabinet. The cost of setting up a new procedure and of the compounding was evaluated in different categories (materials, checking, staff). Results: 228 bags were produced during the 20 days on which we could not obtain the 500 mL bottles (19 batches of 12 bags). The cost of one 250 mL compounded bag was €44.23 (materials: 25.5, checking: €5.73, staff: €13). In addition, developing the system cost €4, 237.72. The overall additional cost was therefore €155.22/L. Conclusions: Despite a major additional cost, compounding calcium gluconate bags has ensured the continued production of TPN. From a risk assessment point of view, identification of several suppliers and increasing our stocks of the raw materials would make out-of-stock situations easier to manage in future. No conflict of interest.